2020
DOI: 10.1001/jamaophthalmol.2019.4502
|View full text |Cite
|
Sign up to set email alerts
|

Individual Risk Prediction for Sight-Threatening Retinopathy of Prematurity Using Birth Characteristics

Abstract: IMPORTANCE To prevent blindness, repeated infant eye examinations are performed to detect severe retinopathy of prematurity (ROP), yet only a small fraction of those screened need treatment. Early individual risk stratification would improve screening timing and efficiency and potentially reduce the risk of blindness. OBJECTIVES To create and validate an easy-to-use prediction model using only birth characteristics and to describe a continuous hazard function for ROP treatment. DESIGN, SETTING, AND PARTICIPANT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
48
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 35 publications
0
48
3
1
Order By: Relevance
“…The present study validated the DIGIROP-Birth model in Chinese preterm infants, and found that the model had less satisfactory performance than previously reported (AUC = 0.634 in this study vs. AUC = 0.85 in the study by Pivodic et al) [23].…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…The present study validated the DIGIROP-Birth model in Chinese preterm infants, and found that the model had less satisfactory performance than previously reported (AUC = 0.634 in this study vs. AUC = 0.85 in the study by Pivodic et al) [23].…”
Section: Discussioncontrasting
confidence: 59%
“…The cutoff value that resulted in the maximal sum of sensitivity and speci city was chosen and assessed. In addition, the cutoff values previously tested by Pivodic et al were also selected for validation [23]. The performance of the DIGIROP-Birth model for identifying TR-ROP infants was also evaluated by gestational age and birth weight.…”
Section: Discussionmentioning
confidence: 99%
“…Although various studies have been conducted from a clinical perspective to prevent blindness caused by ROP, including the identification of risk factors, development of predictive models, and diagnosis of the disease stage with artificial intelligence [ 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ], this review will focus on the translational research that has progressed from basic research to clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…Majority show high sensitivity and medium to low specificity ( 7 10 ). Authors themselves have made clarifications regarding their own models, claiming that no predictive model will work properly at a universal level ( 11 ); in many cases newborns of ≥31 weeks or <24 weeks of pregnancy, who quite often show a wide area of non-vascularized retina after birth, are excluded ( 12 ). However, there is not a single model of practical applicability and adaptability currently available in the usual clinical practice ( 13 ) that helps physicians identify newborns with higher risk of severe ROP requiring treatment and guides the planning of checkup frequency.…”
Section: Introductionmentioning
confidence: 99%
“…The DIGIROP model concluded that one of the best variables for predicting risk of requiring ROP treatment is postnatal chronologicalage ( 12 ). Conversely, the Early Treatment for Retinopathy Of Prematurity Study showed that the wider the avascular area (zone I), the higher the risk of requiring treatment ( 14 ).…”
Section: Introductionmentioning
confidence: 99%